Pengaruh Larutan Natrium Hidroksida Terhadap Kekuatan Komposit Serat Sabut Kelapa - Yan Kondo; Muhammad Arsyad; Muhammad Rusdi; Ilyas Mansur; Muhammad Jufri Dullah (Politeknik Negeri Ujung Pandang, 2022)
Abstract: The purpose of this study was to determine the effect of soaking coconut fiber in sodium hydroxide solution on the strength of the coconut fiber composite. This research was divided into several stages, namely: preparation of materials and tools, the process of soaking coconut fiber, making coconut fiber composites, testing the tensile and flexural properties of coconut fiber composites, and analyzing the test results. Coconut fiber is soaked in sodium hydroxide solution, then dried in an oven, then used as a composite reinforcement using BQTN 157 polyester resin with a composition of 5% coconut fiber. Based on the results of the tensile test according to the ASTM D638-03 standard, and the flexural according to the ASTM D790 standard, it was concluded that the process of soaking coco fiber in sodium hydroxide solution of 5%, 10%, 15%, and 20% had not been able to increase the strength of the coco fiber composite with composition of 5% coconut coir fiber compared to the strength of the resin.